Penanaman Pohon Pucuk Merah Sebagai Penghijauan di Desa Ajibaho - Ramadhani, Mastari; Syarifah Ainun Harahap; Rizka Hidayah Husin Lubis; Thessa Herdyana; Emy Hariati; Leni Malinda; Nuri Ramadhan (Unity Academy, 2022)
Trees play an important role in carbon sequestration and the global carbon cycle thereby helping to mitigate climate change. The carbon dioxide cycle maintains the natural balance of atmospheric concentrations. The creation of too many greenhouse gases causes an imbalance with heat trapped in the Earth's atmosphere, increasing the overall average temperature resulting in global warming. Planting red shoots is the reason it is planted because in addition to functioning as a hedge, it also has a fresh fragrance. And can be used for food coloring from the color of the leaves it has. So that people don't just get the benefits of fresh air. This is in line with the government's request that the Indonesian people plant 25 trees as long as they live. Considering that Indonesia is the largest oxygen contributor in the world, good quality oxygen is needed for the survival of living things on this earth. Indonesia also has the most forests, making it the lungs of the world.